On‐Chip Disordered Lasers: On‐Chip Hyperuniform Lasers for Controllable Transitions in Disordered Systems (Laser Photonics Rev. 14(2)/2020). Issue 2 (11th February 2020) - Lin, Ronghui; Mazzone, Valerio; Alfaraj, Nasir; Liu, Jianping; Li, Xiaohang; Fratalocchi, Andrea
Abstract : As described in article number 1800296 by Xiaohang Li, Andrea Fratalocchi, and co‐workers, the image represents an integrated on‐chip lasing platform composed by complex hyperuniform nanostructures created into a semiconductor material that provides a fully controllable lasing action in terms of lasing thresholds, emission frequency, intensity slopes, and laser linewidths. The system takes advantage of the competition effects between order and disorder created via hyperuniformity.